Patterns of treatment, healthcare utilization and costs by lines of therapy in metastatic breast cancer in a large insured US population. (March 2013) - Ray, Saurabh; Bonthapally, Vijayveer; McMorrow, Donna; Bonafede, Machaon; Landsman-Blumberg, Pamela
Aim: Metastatic breast cancer guidelines contain multiple lines of treatment and regimens; however, little data on therapeutic patterns and costs is available from real-world clinical practice. This descriptive study reports chemotherapy and biologic use, healthcare utilization and costs by line of therapy in a large insured US population.Materials & methods: Adult women with newly diagnosed metastatic breast cancer (between 2005 and 2009) were identified from MarketScan® databases containing medical and pharmacy claims of >40 million enrollees insured with >100 US health plans. Descriptive statistics were reported for use, duration and mean per patient per month costs across four lines of therapy.Results: Out of 7767 patients identified (mean [standard deviation] age = 58.2 [12] years), ≥50% received a subsequent line of therapy across the four lines (line 2: n = 4077; line 3: n = 2033; line four: n = 1059). The top two chemotherapies were paclitaxel and capecitabine in lines one and two, and paclitaxel and gemcitabine in lines three and four. The top two biologics were trastuzumab and bevacizumab across the multiple lines of treatments. Duration (mean, standard deviation and median days) varied across multiple lines of treatments: 162.7, 176.9 and 108.0 in line one; 147.5, 146.7 and 99.0 in line two; 139.9, 131.1 and 99.0 in line three; and 130.9, 123.4 and 94.0 in line four, respectively. Mean per patient per month costs decreased with increasing follow-up from US$13, 147 (<6 months) to US$11, 610 (7–12 months) to US$10, 219 (12–24 months) to US$9, 192 (24–36 months) to US$7, 384 (>36 months). Cumulative costs increased with follow-up, from US$78, 882 (<6 months) to US$443, 062 (>36 months).Conclusion: Longer follow-up, regardless of number of lines of therapy, was associated with higher cumulative, but lower monthly, costs. Delaying progression and improving survival with more individualized treatment regimens may help slow the rate of increasing long-term costs of metastatic breast cancer treatment and care.